2003
DOI: 10.1295/polymj.35.411
|View full text |Cite
|
Sign up to set email alerts
|

High Compatibility of the Poly(oxypropylene)amine-Intercalated Montmorillonite for Epoxy

Abstract: ABSTRACT:The poly(oxypropylene)amine (POP-amine) intercalated montmorillonite (MMT) was found to have a high organophilicity and compatibility with epoxy materials. The 2000 g mol −1 molecular weight POP-amine modified MMT, analyzed to have 63 w% organics and 58.0 Å X-ray diffraction (XRD) d-spacing, was compounded with a curing agent (Jeffamine R D2000) and an epoxy resin (diglycidyl ether of bisphenol A). With 1-10 w% organoclay additions, the cured epoxies exhibited an exfoliated characteristic and signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…In the literature, 18,20 Na + -MMT is generally exfoliated in the polymer-surrounded matrix and hence only possibly observed in the shape of interlayer lines from the side view.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, 18,20 Na + -MMT is generally exfoliated in the polymer-surrounded matrix and hence only possibly observed in the shape of interlayer lines from the side view.…”
Section: Resultsmentioning
confidence: 99%
“…Suter et al (2011) found that a polyether diamine with polyoxypropylene chains as backbones, a backbone of three monomer units per charged amine group was the maximum backbone length contributing to the highest inhibition efficiency, which was consistent with our experimental results. The interaction between clay and PEAs is presented in Scheme 1, which was proposed by Lin et al (2003) to explain the interaction between the polymer and montmorillonite, however, also illustrated the clay swelling inhibitive mechanism of PEAs.…”
Section: Inhibitive Mechanism Of Peasmentioning
confidence: 95%
“…An increasing number of studies indicate that the increased hydrophobicity of clay and thus its interaction with the matrix can be achieved by modification of the montmorillonite (MMT) using various aminated polymer‐based polycations9–15 including aminated liquid rubbers, especially polybutadiene16; aminated nitrile rubbers such as ATBN17, 18; and aminated polyoxypropylene (APOP) and polyoxyethylene . 19–22 Most previous studies were devoted to the effect of the polymer‐modification of MMT on its degree of dispersion (exfoliation); the successful application of APOP‐modified MMT in epoxies10, 23–26 indicates that polymer‐intercalated clay may represent an effective type of toughener. Lin and coworkers23 observed the self‐pinning formation of lamellar arrays and enhanced behavior in the case of low‐ T g network.…”
Section: Introductionmentioning
confidence: 99%